Dopamine-induced tyrosine phosphorylation of NR2B (Tyr1472) is essential for ERK1/2 activation and processing of novel taste information - David, Orit; Barrera, Iliana; Chinnakkaruppan, Adaikkan; Kaphzan, Hanoch; Nakazawa, Takanobu; Yamamoto, Tadashi; Rosenblum, Kobi (Frontiers in Molecular Neuroscience, 2014)
Understanding the heterosynaptic interaction between glutamatergic and neuromodulatory synapses is highly important for revealing brain function in health and disease. For instance, the interaction between dopamine and glutamate neurotransmission is vital for memory and synaptic plasticity consolidation, and is known to converge on ERK-MAPK signaling in neurons. Previous studies suggest that dopamine induces NMDA receptor phosphorylation at the NR2B Y1472 subunit, influencing receptor internalization at the synaptic plasma membrane. However, it is unclear whether this phosphorylation is upstream to and/or necessary for ERK1/2 activation, which is known to be crucial for synaptic plasticity and memory consolidation. Here, we tested the hypothesis that tyrosine phosphorylation of NR2B at Y1472 is correlated with ERK1/2 activation by dopamine and necessary for it as well. We find that dopamine receptor D1, but not D2, activates ERK1/2 and leads to NR2BY1472 phosphorylation in the mature hippocampus and cortex. Moreover, our results indicate that NR2B Y1472 phosphorylation is necessary for ERK1/2 activation. Importantly, application of dopamine or the D1 receptor agonist SKF38393 to hippocampal slices from NR2B F1472 mutant mice did not result in ERK1/2 activation, suggesting this site is not only correlated with ERK1/2 activation by dopamine stimulation, but also necessary for it. In addition, NR2B F1472 mice show impairment in learning of attenuation of taste neophobia, but not associative taste learning. Our study shows that the dopaminergic and glutamatergic transmission converge on the NMDA receptor itself, at the Y1472 site of the NR2B subunit, and that this convergence is essential for ERK1/2 activation in the mature brain and for processing new sensory information in the cortex.